The british conservative party and one nation politics - Seawright, David ([S.l.] : Bloomsbury Academic, 2011)
Won the 2011 Prize for best publication on Conservatives and Conservatism awarded by the specialist group 'Conservatives and Conservatism$1 (Bof the UK Political Studies Association.s
Keywords: Conservatism; Conservative Party (Great Britain); Great Britain; Political science